HBI-8000, HUYABIO Lead Clinical Program, Is a Selective Histone Deacetylase Inhibitor With Therapeutic Benefits in Leukemia and in Solid Tumors - Shojaei, Farbod; Goodenow, Bob; Lee, Gloria; Kabbinavar, Fairooz; Gillings, Mireille (Frontiers in Oncology, 2022)
HBI-8000 is a small molecule inhibitor of class I HDACs and has been approved for the treatment of PTCL, ATL and, in combination with exemestane, in a subpopulation of breast cancer . Given the roles of HDACs in normal and cancerous cells, there are currently multiple clinical trials, by HUYABIO International, to test the efficacy of HBI-8000 in monotherapy or in combination settings in leukemias and in solid tumors. The current review is focused on the applications of HDACi HBI-8000 in cancer therapy and its potential in combination with DDR agents.